Frequency of Pseudomonas in Community-Acquired Pneumonia - Adeel , Mohammad; Khan , Zafar Ahmad; Sasoli , Sarfaraz Ahmed; Nasir , Hina; Asmat , Fauzia; Shah , Firasat Ullah (Indus Journal of Bioscience Research, 2025)
Background: An emerging infection in CAP with important clinical ramifications is Pseudomonas aeruginosa. Optimizing treatment requires knowledge of its prevalence, risk factors, and antibiotic resistance. Objective: to ascertain P. aeruginosa prevalence in CAP, evaluate related risk variables, and measure how it affects clinical results. Methods: A qualitative study involving 120 randomly chosen CAP patients were carried out at a Quetta tertiary care hospital. Clinical features were examined when P. aeruginosa was discovered by microbiological testing. Results: In 12.5% of CAP patients, P. aeruginosa was found. These individuals were more likely to die, have longer hospital stays, and be admitted to the intensive care unit. Multiple antibiotic resistance was noted. Conclusion: This study highlights the significant impact of Pseudomonas aeruginosa on the prognosis of patients with community-acquired pneumonia (CAP), particularly concerning hospitalization rates and mortality. Early identification through microbiological testing and assessment of risk factors plays a crucial role in improving outcomes. Given the organism’s known resistance patterns, a more targeted antibiotic therapy is essential, especially for high-risk individuals. In severe cases, combination therapy may be necessary, while empirical treatment should always align with local resistance trends. The implementation of proper antimicrobial stewardship programs is critical to prevent the emergence and spread of further resistance. Findings: These findings underscore the need for personalized and evidence-based treatment strategies and can contribute meaningfully to the formulation of effective CAP management protocols. In regions experiencing rising antibiotic resistance, these insights are especially valuable for guiding clinical decision-making and optimizing patient care in both outpatient and inpatient settings.